Anticancer effects of sodium butyrate on human colon cancer Caco2 cell line - Flora Forouzesh; Saeid Talebi (Fasa University of Medical Sciences, 2018)
Background & Objective: Sodium butyrate (NaBu), a histone deacetylase inhibitor, is an anticancer drug for multiple cancers. The objective of this research is to study the anticancer effects of sodium butyrate on colon cancer Caco2 cell lines. Material & Methods: Caco-2 cell lines were cultured and then treated with various concentrations of NaBu (from 3.125mM to 200mM). After 24h, 48h and 72h incubation, the cytotoxicity was measured by XTT assay. The statistical significance of difference analyzed by one-way ANOVA/Tukey test. Also, in this research, the morphologic changes are considered by invert microscopy. Results: The results showed that NaBu inhibited the growth in a time- and dose-dependent manner. XTT assays showed that treatment with NaBu at high concentrations significantly inhibited the growth of Caco2 cells. After 24, 48 and 72h, IC50 for Caco2 cells were 105, 100 and 43 mM respectively. Results confirmed the anti-proliferative effect of Sodium butyrate on this cell lines. The results of morphological studies indicated that sodium butyrate has a growth inhibitory effect on IC50 concentration and it can arrest the cell cycle. Conclusion: These results demonstrate that butyrate inhibited the growth of colorectal cancer cells. It caused probably cell death via the induction of apoptosis. These findings may open interesting perspectives in human colorectal cancer treatment strategy.